Effects of Rumensin or Lasalocid on rumen fermentation in vitro - Bartley, E.; Herod, E.; Bechtle, R.; Sapienza, D.; Brent, B. (Kansas State University. Agricultural Experiment Station, 2011)
A series of artificial-rumen studies tested effects of Rumensin and lasalocid on rumen fermentation. At concentrations of 22, 44, and 66 ppm both depressed microbial protein synthesis. Both severely inhibited protein synthesis at 176 ppm. Both increased propionic acid and decreased acetic acid concentrations. However, only Rumensin increased lactic acid. Both inhibited total gas production and decreased the percentage of methane. We concluded that lasalocid and Rumensin have similar effects on rumen fermentation.
Keywords: Beef; Rumen; Fermentation; In vitro